A Model for Sustaining Health at the Primary Care Level. Issue 2 (3rd April 2019) - Sanderson, Alyssa; West Jr., Daniel J.
Abstract: As the healthcare industry in USA is changing from a fee-for-service to a value-based system, the need for a shift in how patients are treated is evident. Healthcare organizations are reimbursed based on value and quality of service. The system shift recognizes that each patient possesses differing medical needs moving care from generalized medical treatments to individualistic care. To deal with this change and attempt to increase quality and value, many healthcare organizations are adopting a team care approach through the development of Patient-Centered Medical Homes (PCMH). In many examples of the team approach, the Primary Care Practitioner (PCP) is viewed as the main coordinator of care. Having this responsibility can create added stress for practitioners, which can lead to a decrease in the quality of care. The proposed model, in this article, outlines an example of how individualistic care can be achieved and assembled in the PCMH with the PCP as the main coordinator of care to sustain patient health.